An overview of oil palm fibre - polymer composites - Mohamed Yusoff, Mohd Zuhri; Salit, Mohd Sapuan; Ismail, Napsiah (2009)
Oil palm fibre was one of the natural fibre that is been widely used in polymer composites. The development and mechanical properties of oil palm fibre - polymer composites is been reviewed in this paper. Result and discussion carried out by various researchers has been studied. Thermosetting and thermoplastic resins are used as matrices in oil palm fibre composites.